Beyond Social Category Cues: Implicit Evaluations of Faces Based on Attractiveness, Character Information, and Minimal Group Membership Influence Emotion Perception - Lindeberg, Sofie Helena (Curtin University, 2020)
Facial expressions of positive emotions are recognized faster than negative expressions. This happy face advantage is larger for faces belonging to more positively evaluated social groups, for instance young or female faces. The current research demonstrated that this influence on emotion recognition is not limited to facial cues signalling social categories. It is also found for attractive faces and faces recently associated with positive character information or belonging to an artificially created social ingroup.